Предмет: Математика,
автор: korwalol
помогите пожалуйста со вторым заданием
Приложения:
![](https://files.topotvet.com/i/373/3736cc3c5972eab5f96ec2296f443cb0.jpg)
Ответы
Автор ответа:
0
(√a+√b)/(a√b-b√a) -(√a-√b)/(a√b+b√a) -3/(a-b)=
=[(√a+√b)·(a√b+b√a)-(√a-√b)·(a√b-b√a)]/(a²b-b²a)-3/(a-b)=
=(a√ab+ab+ab+b√ab-a√ab+ab+ab-b√ab)/ab(a-b) -3/(a-b)=
=(4ab-3ab)/ab(a-b)=1/(a-b)
=[(√a+√b)·(a√b+b√a)-(√a-√b)·(a√b-b√a)]/(a²b-b²a)-3/(a-b)=
=(a√ab+ab+ab+b√ab-a√ab+ab+ab-b√ab)/ab(a-b) -3/(a-b)=
=(4ab-3ab)/ab(a-b)=1/(a-b)
Похожие вопросы
Предмет: Русский язык,
автор: dasha599193
Предмет: Биология,
автор: naurzbaevamedina
Предмет: Английский язык,
автор: KlarkBiner
Предмет: Геометрия,
автор: кавказ57